Literatura i viatge a l'època moderna Una aproximació a alguns itineraris d'autors, personatges i textos per espais reals i imaginaris. - VALSALOBRE, PEP (Scripta)
This study provides an overview (though by no means an exhaustive one) of the relationship between the literature produced by authors from Catalan-speaking territories and their travels in the early modern period, in any language. In the first instance it employs the conventional format of real travellers who produced express texts about these journeys (to the Holy Land or to other destinations with different objectives), and it includes: touring stories inserted into other texts such as diaries and memoirs; trips made for political and diplomatic reasons (with written, literary or non-written expression); and, finally, scientific journeys. Secondly, there are those who travelled through obligation and who did not always leave written testimony of their migration, even if this did result in a significant collection of literary works. Then there is the personal journey undertaken by individuals, whether in the real world or an invented or allegorical one (dreams, myths and beyond). And finally the text itself also undertakes a voyage. The panorama offered here aims to constitute a more descriptive approach to the wealth of materials in this facet of our written culture than an article with great contributions to literary research. It portrays a possible landscape of early modern literature in territories where Catalan was spoken from the perspective of pathways taken (by authors, characters, works).